Sistem Informasi Akademik Berbasis Web Pada Lembaga Bimbingan Belajar Be Excellent Pacitan - Liatmaja, Rizka; Wardati, Indah Ully (IJNS - Indonesian Journal on Networking and Security, 2013)
Abstracts - In the process of organizing academic activities required the presence of a speed and accuracy in data processing. This is necessary in order to improve the quality of services for educate students are the main priority of Be Excellent Tutoring Institute Pacitan. Therefore, in this study will be developed in an academic management system by selecting Be Excellent Tutoring Institute Pacitan as an object of research. Academic information system is referred to as the Academic Information System Be Excellent (SIAKAD Be Excellent) that includes information about the value that includes the value of UTS, UAS values​​, ​​tryout values, points and schedules that include tutoring schedules, UTS schedules, UAS schedules and tryout schedules.The main objective of this study is to produce a web-based academic information system more integrated to support the performance management of academic and as a reference for the institute in conducting performance improvement that has not been optimized so as to improve service to educate students.The results of this study can be used as a response to the difficulties often faced by academic administrators and educate students so that the management of data and presentation of academic information can be more effectively and efficiently. Keywords : Academic Information System, Web Based   Abstraksi - Dalam proses penyelenggaraan kegiatan akademik dituntut adanya suatu kecepatan dan keakuratan dalam pengolahan data. Hal ini diperlukan sebagai upaya untuk meningkatkan mutu pelayanan bagi siswa didik yang merupakan prioritas utama Lembaga Bimbingan Belajar Be Excellent Pacitan. Oleh karena itu, dalam penelitian ini akan dikembangkan suatu sistem pengelolaan akademik dengan memilih Lembaga Bimbingan Belajar Be Excellent sebagai obyek penelitian. Sistem informasi akademik ini disebut sebagai Sistem Informasi Akademik Be Excellent (SIAKAD Be Excellent) yang meliputi informasi tentang nilai yang meliputi nilai UTS, nilai UAS, nilai tryout, point serta jadwal yang meliputi jadwal les, jadwal UTS, jadwal UAS dan jadwal tryout. Tujuan utama penelitian ini yaitu untuk menghasilkan sistem informasi akademik berbasis web yang lebih terintegrasi untuk dapat mendukung kinerja pengelola akademik ataupun sebagai acuan bagi pihak lembaga dalam melakukan perbaikan kinerja yang belum optimal sehingga dapat meningkatkan pelayanan terhadap siswa didik. Hasil dari penelitian ini dapat dijadikan sebagai jawaban terhadap kesulitan yang seringkali dihadapi oleh pengelola akademik maupun siswa didik sehingga pengelolaan data-data maupun penyajian informasi akademik bisa lebih efektif dan efisien. Kata Kunci : Sistem Informasi Akademik, Berbasis Web